Formal α-trifluoromethylthiolation of carboxylic acid derivatives via N-acyl pyrazoles. Issue 20 (12th February 2020) - Franco, Francesca; Meninno, Sara; Benaglia, Maurizio; Lattanzi, Alessandra
Abstract : A direct and general one-pot approach to α-trifluoromethylthiolated amides, esters and carboxylic acids has been successfully developed under mild, catalytic and metal-free conditions. Abstract : Herein we disclosed a one-pot two-step protocol for the first direct, base-catalyzed α-trifluoromethylthiolation of carboxylic acid derivatives by using readily available N -acyl pyrazoles, N -(trifluoromethylthio)phthalimide and a nucleophile such as amines, alcohols and water. Straightforward elaboration of the products to alcohols and triflones expands further the synthetic utility of the process.